Peningkatan Kinerja Tenaga Kependidikan Melalui, Pendidikan, Kompetensi, Dan Knowladge Sharing Dalam Penerapan Sistem Informasi Akademik : (Studi Kasus di Universitas Darul Ulum Islamic Centre Sudirman GUPPI) - Isrofiati, Isrofiati; Kurniati, Edy Dwi; Nurmiyati, Nurmiyati (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
In the increasingly rapid development of information technology, the education sector is experiencing the digital transformation, such as academic information systems (Siakad). Siakad is an academic system built to make easy to be used for academic users, in order to doing some academic activities. This study intented to assess the performance of educational staff through education, competence, and knowledge sharing in the implementation of the Academic Information System in Darul Ulum Islamic Centre Sudirman GUPPI University. A survey-based research method was used in this study, involving 45 respondents from the total educational staff. Data were collected by distributing a questionnaire by google form to all educational staff using a likerts scale. The data analysis method employed was multiple linear regression with the aid of IBM SPSS Statistic 25 version. The results of this study indicate that the variables of education have a significant value of (0,30<0.05), indicating that Ha is accepted and Ho is rejected. This means that the education variable significantly affects the performance of the academic information system. Similarly, the competence variable have a significance value of (0,25<0,05 indicating that Ha is accepted and Ho is rejected. This means that the competence variable significantly affects the performance of the academic information system. Howeve,r the knowledge sharing variable have a significance value of (0,87>0,05), resulting in the rejection of Ha and the acceptance of Ho, indicating that knowledge sharing does not significantly affect the performance of the academic information system. Keywords: iEducation, iCompetence, iKnowledge iSharing, iAcademic iInformation iSystem (Siakad)